Pharmacological evaluation of leaves of Jatropha curcas L. for anti-diabetic activity in alloxan induced diabetic rats - KUMAR, JOSH; SINGH, SATYA PAL; CHOUDHARY, GOVIND KUMAR (The Indian Journal of Animal Sciences, 2016)
Antidiabetic activity of hydroethanolic extract of Jatropha curcas leaves was evaluated using 25 rats equally divided into five groups of five rats each. Group 1 served as healthy control and group 2 as negative control. The study was conducted for the antidiabetic property evaluation after single injection of alloxan drug @ 100 mg/kg b.wt., i.p followed after 48 h by the treatment with the metformin (300 mg/kg) in group 3, hydroethanolic extract of Jatropha curcas leaves (JCE) (200 mg/kg) in group 4 and JCE (400 mg/kg) in group 5. Significant decrease was observed in haematological values of group 2. These values were significantly increased in groups 3 and 5. Total serum protein and albumin values were significantly reduced in group 2 as compared to group 1. But, significant increase was observed in group 3 and 5 in comparison to group 2. A significant increase in serum creatinine, urea, cholesterol, enzymes in group 2 and it significantly reduced in group 3 and group 5. Blood glucose level was significantly increased in group 2 as compared to group 1. Metformin and JCE treated groups had significantly reduced blood glucose level in comparison to group 2. In group 2, LPO level was significantly increased in RBC, liver and kidney but GSH levels were decreased significantly in RBCs, kidney and liver in comparison to group 1. LPO was significantly decreased in kidney and RBCs of group 3 and 5, but there was significant increase in GSH level in liver and RBCs of the group 3 in comparison to group 2.